Creatine supplementation strategies aimed at acutely increasing and maintaining skeletal muscle total creatine content in healthy, young volunteers - Pittas George; Miller Jan; Laithwaite David; Greenhaff Paul (Translational Exercise Biomedicine)
Insight regarding dietary creatine (Cr) supplementation strategies to acutely increase and maintain muscle total creatine (TCr) content is missing.